The Churches of Christ in the twentieth century : Homer Hailey's personal journey of faith - Harrell, David Edwin (Religion and American culture (Tuscaloosa, Ala.), 2000)
"A nondenominational movement of autonomous congregations, Churches of Christ have been among the fastest-growing religious bodies in the 20th century. Throughout the movement's history, church leaders debated issues ranging from missionary societies to the use of instrumental music in worship. Although some disagreements affected only the ties between congregations, others led to the creation of three distinct groups calling themselves Churches of Christ identified by their sociological and theological positions."--Jacket